ANALISIS TINGKAT PEMAHAMAN PENYUSUNAN MODUL AJAR BERDIFERENSIASI MELALUI BIMTEK PADA GURU SMA N 3 SEUNAGAN - Rufa hera; Rita Oktavia (Jurnal Bionatural, 2024)
The purpose of this study was to analyze the level of understanding ofdifferentiated teachers in the preparation of teaching modules at SMA 3 Negeri Seunagan.This research was conducted from May to October 2024 at SMA Negeri 3 Seunagan with theobject of all SMA N 3 Seunagan teachers. The reason researchers chose this school is that oneof the high schools in Nagan Raya Regency has superior accreditation and has implemented an independent learning curriculum. The focus of this research is to get an overview of theteacher's ability to develop differentiated teaching modules. The method used in this researchis a qualitative method. This method is intended to understand the phenomenon of what isexperienced by the research subject such as behavior, perception, motivation, action, andothers holistically and by means of descriptions in the form of words and language, in aspecial natural context by utilizing various natural methods (Moleong, 2017). Qualitativeresearch according to Hendryadi, et. al, (2019) is a naturalistic inquiry process that seeks adeep understanding of social phenomena in a natural way. The data analysis techniques usedare reducing data, selecting data, describing data, presenting data, and concluding data.Reducing data is, “Activities summarize, select key things, focus on important things, look forthemes and patterns and discard unnecessary ones” (Sugiyono, 2009: 338). The final stage isto make conclusions from the data that has been described. The stage of analyzing data is themost important stage because this is to give meaning to the data that has been collected. Fromthe results of the interview, it can be obtained that before and after the Technical Guidancewas carried out, it can be seen that the improvement of teachers about differentiation andpreparation of teaching modules is better or more understanding. Although there are severalindicators of questions that teachers still cannot answer. But in general, technical guidance inimproving understanding of the preparation of differentiated teaching modules has beensuccessful.